CDN - ale jaki? . [dod. po wydaniu nr 200]. CDN Głos Wolnego Robotnika, June 1987 (Dodatek) - Międzyzakładowy Robotniczy Komitet "Solidarności" w Warszawie ([s.n.], 1987)
Creation and circulation: For issues no. 1-80 edition A assumed to be the primary edition.Published in variations: editions B,C,D,E,F. From issue no. 81 published without variations and omiting the edition statement